High performance Ce-doped ZnO nanorods for sunlight-driven photocatalysis - Chouchene, Bilel; Ben Chaabane, Tahar; Balan, Lavinia; Girot, Emilien; Mozet, Kevin; Medjahdi, Ghouti; Schneider, Raphaël (Beilstein Journal of Nanotechnology, 2016)
Ce-doped ZnO (ZnO:Ce) nanorods have been prepared through a solvothermal method and the effects of Ce-doping on the structural, optical and electronic properties of ZnO rods were studied. ZnO:Ce rods were characterized by XRD, SEM, TEM, XPS, BET, DRS and Raman spectroscopy. 5% Ce-doped ZnO rods with an average length of 130 nm and a diameter of 23 nm exhibit the highest photocatalytic activity for the degradation of the Orange II dye under solar light irradiation. The high photocatalytic activity is ascribed to the substantially enhanced light absorption in the visible region, to the high surface area of ZnO:Ce rods and to the effective electron–hole pair separation originating from Ce doping. The influence of various experimental parameters like the pH, the presence of salts and of organic compounds was investigated and no marked detrimental effect on the photocatalytic activity was observed. Finally, recyclability experiments demonstrate that ZnO:Ce rods are a stable solar-light photocatalyst.
Keywords: Ce doping; photocatalysis; solvothermal synthesis; ZnO rods

(untitled) - Fujishima, A.; Honda, K. (Nature, 1972)

(untitled) - Li, L.; Liu, X.; Zhang, Y.; Nuhfer, N. T.; Barmak, K.; Salvador, P. A.; Kohrer, G. S. (ACS Appl. Mater. Interfaces, 2013)

(untitled) - Navaveni, K.; Silvalingam, G.; Edge, M. S.; Madros, G. (Environ. Sci. Technol., 2004)

(untitled) - Linsebrigler, A. L.; Lu, G.; Yates, J. T. (Chem. Rev., 1995)

(untitled) - Achouri, F.; Corbel, S.; Aboulaich, A.; Balan, L.; Ghrabi, A.; Ben Said, M.; Schneider, R. (J. Phys. Chem. Solids, 2014)

(untitled) - Dong, S.; Feng, J.; Fan, M.; Pi, Y.; Hu, L.; Han, X.; Liu, M.; Sun, J.; Sun, J. (RSC Adv., 2015)

(untitled) - Moussa, H.; Girot, E.; Mozet, K.; Alem, H.; Medjahdi, G.; Schneider, R. (Appl. Catal., B: Environ., 2016)

(untitled) - Ullah, R.; Dutta, J. (J. Hazard. Mater., 2008)

(untitled) - Gouvêa, C. A. K.; Wypych, F.; Moraes, S. G.; Durán, N.; Peralta-Zamora, S. (Chemosphere, 2000)

(untitled) - Ahmad, M.; Ahmed, E.; Zhang, Y.; Khalid, N. R.; Xu, J.; Ullah, M.; Hong, Z. (Curr. Appl. Phys., 2013)

(untitled) - Liu, S.; Li, C.; Yu, J.; Xiang, Q. (CrystEngComm, 2011)

(untitled) - Barick, K. C.; Singh, S.; Aslam, M.; Bahadur, D. (Microporous Mesoporous Mater., 2010)

(untitled) - Achouri, F.; Corbel, S.; Balan, L.; Mozet, K.; Girot, E.; Medjahdi, G.; Ben Said, M.; Ghrabi, A.; Schneider, R. (Mater. Des., 2016)

(untitled) - Cheng, B.; Xiao, Y.; Wu, G.; Zhang, L. (Appl. Phys. Lett., 2004)

(untitled) - Cheng, B. C.; Xiao, Y. H.; Wu, G. S.; Zhang, L. D. (Adv. Funct. Mater., 2004)

(untitled) - Hamadani, N. F.; Mahjoub, A. R.; Khodadadi, A. A.; Mortazavi, Y. (Sens. Actuators, B, 2012)

(untitled) - Yang, J.; Gao, M.; Yang, L.; Zhang, Y.; Lang, J.; Wang, D.; Wang, Y.; Liu, H.; Fan, H. (Appl. Surf. Sci., 2008)

(untitled) - Ge, C.; Xie, C.; Cai, S. (Mater. Sci. Eng., B, 2007)

(untitled) - Li, G.-R.; Lu, X.-H.; Zhao, W.-X.; Su, C.-Y.; Tong, Y.-X. (Cryst. Growth Des., 2008)

(untitled) - George, A.; Sharma, S. K.; Chawla, S.; Malik, M. M.; Qureshi, M. S. (J. Alloys Compd., 2011)

(untitled) - Tan, W. K.; Razak, K. A.; Lockman, Z.; Kawamura, G.; Muto, H.; Matsuda, A. (Opt. Mater., 2013)

(untitled) - Wan, G. X.; Ma, S. Y.; Li, X. B.; Li, F. M.; Bian, H. Q.; Zhang, L. P.; Li, W. Q. (Mater. Lett., 2014)

(untitled) - Zhang, Y. G.; Zhang, G. B.; Wang, Y. X. (J. Appl. Phys., 2011)

(untitled) - Lang, J.; Han, Q.; Yang, J.; Li, C.; Yang, L.; Zhang, Y.; Gao, M.; Wang, D.; Cao, J. (J. Appl. Phys., 2010)

(untitled) - Jung, Y.-I.; Noh, B.-Y.; Lu, Y.-S.; Back, S.-H.; Kim, J. H.; Park, I.-K. (Nanoscale Res. Lett., 2012)

(untitled) - Dar, G. N.; Umar, A.; Zaidi, S. A.; Ibrahim, A. A.; Abaker, M.; Baskoutas, S.; Al-Assiri, M. S. (Sens. Actuators, B, 2012)

(untitled) - Sinha, N.; Ray, G.; Bhandari, S.; Godara, S.; Kumar, B. (Ceram. Int., 2014)

(untitled) - Karunakaran, C.; Gomathisankar, P.; Manikandan, G. (Mater. Chem. Phys., 2010)

(untitled) - Faisal, M.; Ismail, A. A.; Ibrahim, A. A.; Bouzid, H.; Al-Sayari, S. A. (Chem. Eng. J., 2013)

(untitled) - Djaja, N. F.; Saleh, R. (Mater. Sci. Appl., 2013)

(untitled) - Yayapao, O.; Thongtem, S.; Phuruangrat, A.; Thongtem, T. (Ceram. Int., 2013)

(untitled) - Rezaei, M.; Habibi-Yangjeh, A. (Appl. Surf. Sci., 2013)

(untitled) - Liang, Y.; Guo, N.; Li, L.; Li, R.; Ji, G.; Gan, S. (RSC Adv., 2015)

(untitled) - Anandan, S.; Miyauchi, M. (Phys. Chem. Chem. Phys., 2011)

(untitled) - Subash, B.; Krishnakumar, B.; Velmurugan, R.; Shanti, M. (Catal. Sci. Technol., 2012)

(untitled) - Seddigi, Z. S.; Bumajdad, A.; Amsari, S. P.; Ahmed, S. A.; Danish, E. Y.; Yarkandi, N. H.; Ahmed, S. (J. Hazard. Mater., 2014)

(untitled) - Lam, S.-M.; Sin, J.-C.; Satoshi, I.; Abdullah, A. Z.; Mohamed, A. R. (Appl. Catal., A, 2014)

(untitled) - Hsu, M.-H.; Chang, C.-J. (J. Hazard. Mater., 2014)

(untitled) - Fang, J.; Fan, H.; Dong, G. (Mater. Lett., 2014)

(untitled) - Rajbongshi, B. M.; Samdarshi, S. K. (Mater. Sci. Eng., B, 2014)

(untitled) - Khanchandani, S.; Srivestava, P. K.; Kumar, S.; Ghosh, S.; Ganguli, A. K. (Inorg. Chem., 2014)

(untitled) - McLaren, A.; Valdes-Solis, T.; Li, G.; Tsang, S. C. (J. Am. Chem. Soc., 2009)

(untitled) - Zheng, Y.; Chen, C.; Zhan, Y.; Lin, X.; Zheng, Q.; Wei, K.; Zhu, J.; Zhu, Y. (Inorg. Chem., 2007)

(untitled) - Wu, D.; Wang, W.; Tan, F.; Sun, F.; Lu, H.; Qiao, X. (RSC Adv., 2013)

(untitled) - Peng, Y.; Qin, S.; Wang, W.-S.; Xu, A.-W. (CrystEngComm, 2013)

(untitled) - Akhavan, O.; Mehrabian, M.; Mirabbaszadeh, K.; Azimirad, R. (J. Phys. D: Appl. Phys., 2009)

(untitled) - Baruah, S.; Abbas Mahmood, M.; Zar Myint, M. T.; Bora, T.; Dutta, J. (Beilstein J. Nanotechnol., 2010)

(untitled) - Qiu, X.; Li, G.; Sun, X.; Li, L.; Fu, X. (Nanotechnology, 2008)

(untitled) - Alim, K. A.; Fonoberov, V. A.; Shamsa, M.; Baladin, A. A. (J. Appl. Phys., 2005)

(untitled) - Shyu, J. Z.; Waber, W. H.; Gandhi, H. S. (J. Phys. Chem., 1988)

(untitled) - Francisco, M. S. P.; Mastelaro, V. R.; Nascente, P. A. P.; Florentino, A. O. (J. Phys. Chem. B, 2001)

(untitled) - Burroughs, P.; Hamnett, A.; Orchard, A. F.; Thornton, G. (J. Chem. Soc., Dalton Trans., 1976)

(untitled) - Pfau, A.; Schierbaum, K. D. (Surf. Sci., 1994)

(untitled) - Iqbal, J.; Liu, X.; Zhu, H.; Wu, Z. B.; Zhang, Y.; Yu, D.; Yu, R. (Acta Mater., 2009)

(untitled) - Singh, K. S. W.; Everett, D. H.; Haul, R. A. W.; Moscou, L.; Pierotti, R. A.; Rouquerol, J.; Siemieniewska, T. (Pure Appl. Chem., 1985)

(untitled) - Behnajady, M. A.; Modirshahla, N.; Hamzawi, R. (J. Hazard. Mater., 2006)

(untitled) - Aghedach, A.; Brosillon, S.; Morvan, J.; Chadi, E. K. (J. Hazard. Mater., 2008)

(untitled) - Hu, C.; Yu, J. C.; Hao, Z.; Wong, P. K. (Appl. Catal., B: Environ., 2003)

(untitled) - Ou, Y.; Lin, J.-D.; Zou, H.-M.; Liao, D.-W. (J. Mol. Catal. A: Chem., 2005)

(untitled) - Yin, M.; Li, Z.; Kou, J.; Zou, Z. (Environ. Sci. Technol., 2009)

(untitled) - Kominami, H.; Iwasaki, S.-i.; Maeda, T.; Imamura, K.; Hashimoto, K.; Kera, Y.; Ohtani, B. (Chem. Lett., 2009)